2018
DOI: 10.3389/fevo.2018.00145
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Utility of Single Nucleotide Polymorphism Markers to Reveal Fine-Scale Population Structure in Human Malaria Parasite Plasmodium falciparum

Abstract: Single nucleotide polymorphisms (SNPs) have been shown to be useful in revealing population structure with continental-and regional-scale samples. In epidemiological study, a careful selection of SNPs to track disease spread in local communities would provide an important addition to traditional disease surveillance. This study used SNPs and microsatellites to examine population structure of Plasmodium falciparum at fine-scale in malaria-endemic areas of Western Kenya. A set of high performance (HP) SNPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 100 publications
1
12
0
1
Order By: Relevance
“…Hence, SNPs play a vital role in tracking virus strains and variations. Analysis of SNP was carried out in ( Lo et al, 2018 ) as well where they suggested a change in the samples of Plasmodium falciparum between the northern and southern regions of Western Kenya; the samples from the southern part showed lesser divergence from each other. Furthermore, clustering has been used by many studies ( Sevilla-Reyes et al, 2013 , Fischer et al, 2018 , Hahn et al, 2020 ) to understand genetic characteristics for a large set of genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, SNPs play a vital role in tracking virus strains and variations. Analysis of SNP was carried out in ( Lo et al, 2018 ) as well where they suggested a change in the samples of Plasmodium falciparum between the northern and southern regions of Western Kenya; the samples from the southern part showed lesser divergence from each other. Furthermore, clustering has been used by many studies ( Sevilla-Reyes et al, 2013 , Fischer et al, 2018 , Hahn et al, 2020 ) to understand genetic characteristics for a large set of genomes.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of various estimators of F ST have been studied extensively and there is a rich and longstanding literature on IBD [ 15 ]. However, there is currently only limited guidance on the size [ 5 ] and type [ 16 ] of genetic data needed for measuring gene flow between malaria parasite populations, and none specific to the questions of ranking and classification. Most studies of this kind use genetic data of widely varying sizes and types, including both whole genome sequence data and SNP ‘barcode’ data (typically consisting of 24- to 100-SNPs [ 17 , 18 ]), limiting generalizability and comparability between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) are the popular subjects in the population studies, because of their high frequencies, low cost, and ease of evaluation and analysis methods 18 . MTOR gene, located on the long arm of human chromosome 1 (1q36.2), consists of 3,434 genetic polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Single nucleotide polymorphisms (SNPs) are the popular subjects in the population studies, because of their high frequencies, low cost, and ease of evaluation and analysis methods. 18 MTOR gene, located on the long arm of human chromosome 1 (1q36.2), consists of 3,434 genetic polymorphisms. rs2295080 (T > G) in the promoter region and rs2536 T > C in the 3 0 -untranslated region (3 0 UTR) of MTOR gene are well-evaluated SNPs of this gene.…”
mentioning
confidence: 99%